A modelling approach for the nonlinear dynamics of assembled structures undergoing fretting wear. (29th March 2019) - Armand, J.; Pesaresi, L.; Salles, L.; Wong, C.; Schwingshackl, C. W.
Abstract : Assembled structures tend to exhibit nonlinear dynamic behaviour at high excitation levels due to the presence of contact interfaces. The possibility of building predictive models relies on the ability of the modelling strategy to capture the complex nonlinear phenomena occurring at the interface. One of these phenomena, normally neglected, is the fretting wear occurring at the frictional interface. In this paper, a computationally efficient modelling approach which enables considerations of the effect of fretting wear on the nonlinear dynamics is presented. A multi-scale strategy is proposed, in which two different time scales and space scales are used for the contact analysis and dynamic analysis. Thanks to the de-coupling of the contact and dynamic analysis, a more realistic representation of the contact interface, which includes surface roughness, is possible. The proposed approach is applied to a single bolted joint resonator with a simulated rough contact interface. A tendency towards an increase of real contact area and contact stiffness at the interface is clearly observed. The dynamic response of the system is shown to evolve over time, with a slight decrease of damping and an increase of resonance frequency, highlighting the impact of fretting wear on the system dynamics.